1980
DOI: 10.1590/s1679-87591980000200058
|View full text |Cite
|
Sign up to set email alerts
|

"Standing crop" na área estuarina SW da Baía de Todos os Santos

Abstract: The present study is intended to evaluate the potential of an estuarine area surrounded by mangrove at Todos os Santos Bay (Bahia State, Brazil), for supporting aquaculture activities. From October 1977 to July 1978 samples were collected monthly on alternate tides for determination of particulate organic carbon and total proteins The following environmental parameters were also considered: salinity. temperature, pH, transparence, dissolved oxygen, silicates, ammonia, nitrites, nitrate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 1 publication
0
1
0
Order By: Relevance
“…org/10.6084/m9.figshare.9759311.v1> environments still to be inventoried. In the case of Bahia, which comprises the most extensive part of the Brazilian coast, little is known about phytoplankton communities; most published studies are concentrated in the Todos os Santos Bay (e.g., Peixinho et al 1980;Cowgill 1987;Mafalda Jr. et al 2003;Magalhães & Barbosa 2008) and Camamu Bay (i.e., . Nevertheless, most studies are not published as research articles and can only be found in academic monographs and dissertations.…”
Section: Introductionmentioning
confidence: 99%
“…org/10.6084/m9.figshare.9759311.v1> environments still to be inventoried. In the case of Bahia, which comprises the most extensive part of the Brazilian coast, little is known about phytoplankton communities; most published studies are concentrated in the Todos os Santos Bay (e.g., Peixinho et al 1980;Cowgill 1987;Mafalda Jr. et al 2003;Magalhães & Barbosa 2008) and Camamu Bay (i.e., . Nevertheless, most studies are not published as research articles and can only be found in academic monographs and dissertations.…”
Section: Introductionmentioning
confidence: 99%